Strategi Pengembangan Usahatani Gula Kelapa Di Kecamatan Puring Kabupaten Kebumen - Wahid Abdil Malik; Minar Ferichani; Emi Widiyanti (Universitas Sebelas Maret, 2018)
This study aims to determine the magnitude of farm income coconut sugar in District Puring Kebumen, knowing internal factors (strengths and weaknesses) and external (opportunities and threats), to formulate a possible strategic alternatives and identifies priorities for the strategy to be applied in the development of farming of palm sugar in District Puring Kebumen. The research method used is descriptive method. Data analysis method used is the Revenue Analysis, Internal Factor Evaluation (IFE), External Factor Evaluation (EFE), SWOT Analysis and QSPM. These results indicate that the amount of income of Rp 37,323,400.00 for the period June 2015 - June 2016. Internal Factor Evaluation (IFE) showed that coconut sugar farm has five strengths and four weaknesses. External Factor Evaluation (EFE) show gardens coconut sugar farm has four opportunities and five threats. SWOT Analysis generate alternative strategies that can be implemented that improve product with open innovation and their consumer confidence, create attractive packaging so that the consumer response is high, increase competitiveness through cooperatives or associations for joint marketing, and to expand the market by leveraging information technology such as the Internet. QSPM produce good strategic priorities to be implemented is to increase competitiveness through cooperatives or associations for joint marketing.